(untitled) (CIPEEX, 2022)
CORONAVIRUS DISEASE 2019 (COVID-19) IS AN EMERGING AND HIGHLY CONTAGIOUS INFECTIOUS DISEASE, WHOSE CLINICAL MANIFESTATIONS AND SEQUELAE ARE PARTIALLY ELUCIDATED. AMONG THE MOST FREQUENT SYMPTOMS OF THIS DISEASE ARE RESPIRATORY, GASTROINTESTINAL AND NEUROLOGICAL, THE LATTER BEING THE MAIN RESPONSIBLE FOR LONG-TERM COMPLAINTS. IT AFFECTS WORKERS OF ALL CATEGORIES, HOWEVER, IN THE PANDEMIC CONTEXT, THOSE WHO WORK IN HOSPITALS ARE MORE VULNERABLE TO CONTAGION AND ARE EXPOSED TO A HIGH VIRAL LOAD. OBJECTIVE: TO DESCRIBE THE NEUROLOGICAL SIGNS AND SYMPTOMS CAUSED BY ACUTE AND SUBACUTE INFECTION BY COVID-19 AND ITS SEQUELAE IN WORKERS AT HOSPITAL ESTADUAL DE ANÁPOLIS DR. HENRIQUE SANTILLO (HEANA), WHO BECAME INFECTED IN 2020, ACCORDING TO SEX AND FUNCTION WITHIN THE UNIT. METHODS: A CROSS-SECTIONAL OBSERVATIONAL STUDY WAS CARRIED OUT, THROUGH THE APPLICATION OF A QUESTIONNAIRE DEVELOPED BY THE TEAM OF RESEARCHERS, TO HEANA WORKERS AFFECTED BY COVID 19 IN 2020. THE RESULTS WERE ANALYZED USING THE CHI-SQUARE TEST SEEKING SIGNIFICANCE <0.05. RESULTS: THE WORKERS PRESENTED DIFFERENT NEUROLOGICAL SIGNS AND SYMPTOMS AT THREE MOMENTS OF THE NATURAL COURSE OF THE DISEASE, WHICH ARE, RESPECTIVELY: HEADACHE, ANOSMIA AND AGEUSIA, IN THE ACUTE CONDITION; MYALGIA, IN CASES 30 DAYS AFTER THE END OF THE INFECTION; AND MEMORY LOSS, IN THE CHRONIC FRAMEWORK OF THE POST-COVID SYNDROME. FURTHERMORE, STATISTICAL VARIATIONS WERE FOUND IN THE PROPORTION OF OCCURRENCE OF SYMPTOMS IN TWO VARIABLES INVESTIGATED BY THE STUDY, NAMELY, GENDER AND THE ROLE OF WORKERS WITHIN THE INSTITUTION. CONCLUSION: THE NEUROLOGICAL SYMPTOMATOLOGY ASSOCIATED WITH COVID-19 INFECTION OCCURS BOTH DURING THE INFECTION AND AFTER ITS TERMINATION, WITH A VARIABLE COURSE OF SYMPTOMS DEPENDING ON THE STAGE, SEX AND JOB POSITION OF THE PATIENT IN THE HEALTH AREA. THUS, THE RELEVANCE OF THE PRESENT WORK IS EMPHASIZED DUE TO ITS SOCIAL IMPORTANCE AND INNOVATIVE CHARACTER, GIVEN THAT THERE ARE STILL FEW INVESTIGATIONS LIKE THIS DESCRIBED IN THE LITERATURE.